Regulação dos gases medicinais no Brasil - Costa, Gustavo Aguiar da (2022)
Different atmospheric gases, such as oxygen, nitrogen and argon - as well as process gases (which arise due to a chemical reaction) and certain gas mixtures - have been used over the years by mankind in a number of industrial and medical applications. Specifically, medical gases – those used in the health area and intended to come into contact with the human body for diagnosis, treatment or prophylaxis – came under regulation by the Brazilian Health Regulatory Agency – Anvisa, with the entry into force of two resolutions on the subject in the first decade of this century. In this context, the present work has as research problem the analysis of the need for regulatory intervention in the medical gases sector. Considering the duty of the State to (i) regulate, supervise and control health activities - provided for in Articles 196 and 197 of the Federal Constitution – and at the same time (ii) avoid the abuse of regulatory power, which was recently established by Law No. 13.874 of September 20th, 2019 (Economic Freedom Act - LLE), as well as (iii) meeting Anvisa's institutional mission to promote the protection of the population's health, by executing sanitary control of both the production and marketing of products and ingredients, the following question is made: is the regulation in the medical gases sector justified? The hypothesis is that, due to the social risks inherent to the activities involving medical gases, the State must exercise its regulatory power and intervene to define technical parameters regarding the manufacturing, filling, distribution and transportation of these products. There are risks to human health and serious accidents involved in the activities. Likewise, there are market failures due to the characteristics of the sector (information asymmetry and externalities, most notably) which justify the need for intervention. On the other hand, the new law introduced by the Economic Freedom Act necessary to mitigate market failures and performed in a rational and proportional way. To test this hypothesis, the work proposes to use the case study regarding the regulation being carried out by Anvisa in Brazil as of the first decade of this millennium concerning medical gases, verifying whether such regulation meets the constitutional duty of the State to regulate, supervise and control health activities and, concurrently, is in line with the Economic Freedom Act. This work also offers a critical analysis and proposes regulatory adjustments to adapt the current regulation, correcting imperfections detected with the purpose of mitigating market failures and, at the same time, observing the legal imposition of minimum intervention in economic activity. In order to discuss the above theme with a real example, a flexibility promoted by the Regulatory Agency during the Covid-19 pandemic will be analyzed, when the minimum purity requirement for medical oxygen manufactured in cryogenic plants outside health facilities was reduced, which reinforced one of the detected adjustments.